Implementasi Pembelajaran Pendidikan Agama Islam dalam Membentuk Karakter Religius di SMA Negeri 1 Patianrowo Nganjuk - Achmad Musyaffa' Putra Tsani; Umiarso; Mukhlis, Fahrudin (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Contemporary Islamic religious education learning needs to adopt several teaching methodologies to increase students' motivation and role in learning according to life practices. The aim of this research is to explore the implementation of PAI learning at the high school level in forming students' religious character. This research uses a qualitative approach with a case study type of research. Data collection techniques using observation, interviews, and documentation of PAI educators, school principals, deputy principals for curriculum, deputy principals for student affairs, and students as research subjects. Research data was analyzed by data reduction based on the results of in-depth interviews. The results of the research show that the implementation of Islamic religious learning in schools is not supported by relevant learning resources and the infrastructure is less supportive. The application of practical methods and strategies supported by film dialogue has an effective impact on the motivational experience for students. The impact of inadequate learning resources affects high school students' Islamic religious education content knowledge literacy. The research implications show that the contribution of the relationship between understanding material content and Islamic religious education learning practices must be supported by educators' scientific capacity pedagogically on an ongoing basis.